Design And Development Of 1064nm Nd: Yag Laser From 808nm Diode Laser Source - Shokrani, Mohammadreza (2009)
Laser technology plays a crucial role in our every day life; in fact, it opens to us new windows and interesting horizon of science. In this respect, Nd:YAG is a crystal which is used as a lasing medium for solid-state lasers. Nd:YAG lasers typically emit light with a wavelength of 1064 nm in the infrared . However, there are also transitions near 940,1120 ,1320, and 1440 nm. Nd:YAG lasers operate in both pulsed and continuous mode. In this master thesis project, a solid-state Nd:YAG laser using diode laser source was built. The project consisted of two parts. The first part is based on a mathematical simulation using a MATLAB modelling. The target of this simulation was to determine graphs for the particles population in multiple gain media like the four-layer Nd:YAG laser, and some environmental coefficients were also incorporated in this modelling. The differential equations describe the population of electrons in the according energy level of the Nd :YAG . They also show the output intensity of the laser. The obtained graphs described the population inversion in the energy levels inside of the Nd :YAG. The characteristics of the intensity output of the laser, during the transient time, can not be monitored by the experimental setup, therefore this was done through the MATLAB simulation. In the second part, a CW diode-pumped solid-state laser was constructed . As a laser gain medium, a Nd:YAG crystal with 1 % Nd doped, lased at 1064nm , was used. 1 Watt L808P1WJ diode laser, with thermoelectric cooler, was used to excite the Nd-YAG rod . The Nd:YAG is still very inefficient in the conversion of input energy, typically the Nd :YAG lasers which are found to achieve only 5 to 1 0% efficiency. Light from the pump laser is generated by the laser diode driver (thorlab PRO 800- with LOC & TEC). The dimension of the Nd-YAG was 5mm diameter x 5mm length, while the mirror property of HT>99.9% @ 808nm and R>95 @ 1 064nm was used . The Monochromator was used to detect the output wavelength of the laser produced. An electrical efficiency of 10.67 % was realized. The optical to optical efficiency is 19.2, with the slope efficiency of 20.2%. Although the optical to optical efficiency and slope efficiency were rather low, the electrical efficiency was considerable.